Architectural Hallucinations: What Can AI Tell Us About the Mind of an Architect?. (7th April 2022) - Leach, Neil
Abstract: Can AI help us to understand how the mind works, and how architects think? Neil Leach, Professor at Florida International University, points out that, although human intelligence and artificial intelligence are very different things, analogies can be drawn. AI, he argues, can potentially offer us insights into how the mind works, and so too into how architects are trained to think.